Indigenous empowerment through human-machine interactions : the challenges and strategies from business lenses - Ghosal, Indrajit; Gupta, Swati; Rana, Sudhir; Saha, Dipak (Emerald Publishing Limited, 2025)
Indigenous communities globally struggle to preserve their cultural heritage amidst a modern landscape shaped by technological advancement and free market capitalism. In today's globalized economy, Indigenous knowledge intersects with domains like finance, artificial intelligence (AI), machine learning (ML), technology, consumer behavior, and the marketing industry. In Indigenous Empowerment through Human-Machine Interactions: The Challenges and Strategies from Business Lenses, an international group of scholars takes an interdisciplinary approach to deciphering the complexities that arise from the convergence of modern technology and traditional Indigenous knowledge. By integrating disciplines such as finance, technology, consumer behavior, and marketing within the context of Indigenous empowerment, this groundbreaking work pioneers new insights into how these elements can synergize for sustainable development. Indigenous Empowerment through Human-Machine Interactions serves as a bridge between academia, policymaking, and Indigenous leadership, offering a practical guide for policymakers and professionals seeking to engage with Indigenous communities in meaningful ways.